Comèl-Netherton's syndrome in siblings - Asha Gowrappala Shanmukhappa; Priyadarshini Kharge; Bhumika Shivaram; Leelavathy Budamakuntala (Wolters Kluwer Medknow Publications, 2016)
The syndrome is characterized by the association of two classical clinical presentations:"Trichorrhexis invaginata", reported by Netherton and the"Ichthyosis linearis circumflexa", described by Comel. Comèl - Netherton syndrome is an autosomal recessive disorder characterized by congenital ichthyosis linearis circumflexa, hair shaft defects, atopy, markedly elevated IgE levels and immune deficiency.1,2,3 It is caused by mutation in Spink5 gene that encodes for protein Latki, which inhibits the enzyme serine proteinase, deficiency of which leads to desquamation of horny layer.4,5 We hereby report this case in a pair of siblings who presented with Ichthyosis linearis circumflexa, trichorrhexis invaginata, pili torti and atopic features. Investigations of skin, hair and blood confirmed the clinical findings. The case is being reported for its rare and classical occurrence.